Documenting information making in archaeological field reports. Issue 5 (29th April 2021) - Huvila, Isto; Sköld, Olle; Börjesson, Lisa
Abstract : Purpose: Sharing information about work processes has proven to be difficult. This applies especially to information shared from those who participate in a process to those who remain outsiders. The purpose of this article is to increase understanding of how professionals document their work practices with a focus on information making by analysing how archaeologists document their information work in archaeological reports. Design/methodology/approach: In total 47 Swedish archaeological reports published in 2018 were analysed using close reading and constant comparative categorisation. Findings: Even if explicit narratives of methods and work process have particular significance as documentation of information making, the evidence of information making is spread out all over the report document in (1) procedural narratives, (2) descriptions of methods and tools, (3) actors and actants, (4) photographs, (5) information sources, (6) diagrams and drawings and (7) outcomes. The usability of reports as conveyors of information on information making depends more on how a forthcoming reader can live with it as a whole rather than how to learn of the details it recites. Research limitations/implications: The study is based on a limited number of documents representing one country and one scholarly and professional field. Practical implications: Increased focus on the internal coherence of documentation and the complementarity of different types of descriptions could improve information sharing. Further, descriptions of concepts that refer to work activities and the situation when information came into being could similarly improve their usability. Originality/value: There is little earlier research on how professionals and academics document and describe their information activities.